Accuracy of DeepL Translation in Inside Out 2 Movie Compared to Official Subtitles - Hasibuan, Sri Wahyuni; Sibarani, Berlin; Sinaga, Dolli Rotua; Siregar, Alfina Gustiany (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to describe the level of translation accuracy produced by DeepL in the film Inside Out 2 and compared it with the official subtitles. Using a qualitative descriptive method, the researcher selected 30 segments from the film's dialogues that contain various expressions, idioms, and contextual meanings. The accuracy of DeepL translations was assessed using the translation quality assessment model developed by Nababan, Nuraeni, and Sumardiono (2012), which classifies translations into three levels: accurate, moderately accurate, and inaccurate. The results showed that most of DeepL's translations felt into the